What Explains the Diversity of Regulatory Reform Outcomes? - Petar Stankov; Aleksandar Vasilev (Global Development Network (GDN), 2015)
We set up a tractable general equilibrium (GE) model to study how output of firms of different size grows after entry and labor reforms. We then take the model predictions to the largest global publicly available firm-level data set: the Enterprise Surveys data. The results demonstrate that firms of different size grow differently after identical reforms. Thus, based on the notable differences of firm-size distributions across countries, identical reforms may produce a variety of growth outcomes.
Keywords: C13; 330; regulatory reform; general equilibrium